Republic of Serbia : Third Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Serbia's Third Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria (PCs). The program is delivering good results. Significant fiscal tightening and efforts to address structural weaknesses and improve the business climate have helped restore growth and boost confidence and foreign direct investment. All end-September PCs were met with significant margins. However, there was a minor deviation in the indicative criterion on domestic arrears, and implementation of structural benchmarks has faced delays. Modifications of the end-December fiscal performance criteria are proposed to allow recognition of past liabilities.